A three year clinical review of the impact of angiotensin converting enzymes inhibitors on the intra hospital mortality of congestive heart failure in Nigerians (1996)
Angiotensin converting enzymes inhibitors are now regarded as the cornerstone of congestive heart failure therapy owing to established reduction in mortality and the symptomatic amelioration following their use. Although the response to converting enzyme inhibitor therapy may be influenced by race, we have reported a trend to reduce intra hospital mortality, the correction of hyponatremia and shortened hospitalization in Nigerians treated with converting enzyme inhibitors. We have now conducted an extended retrospective study, to evaluate the trends in the use of enalapril or captopril and its impact on prognosis in Nigerian patients with heart failure alone, admitted between January 1992 to December 1994. The proportion of heart failure treated with (captopril or enalapril) increased from 37pc in 1992, to 50pc in 1993, to 65pc in 1994. The demographic variables and cause of heart disease were similar in patients treated with converting enzyme inhibitors (n = 55) and those treated conventionally (n = 36). The cumulative mortality among converting enzyme inhibitors treated patients, was (8/55, 14pc) compared to patients not treated (17/36, 48pc) x2 = 12.4; p < 0.0001. There was no sex predilection in mortality (M = 25pc, F = 28pc, mean 27pc). However, initial serum Na+,125mmol was significantly (x2 = 11.1; p < 0.001) more common in the dead patients, 25pc compared to the survivors discharged home 7.5pc. The median hospital stay was 17 days in captopril treated survivors (range two to 44 days) and 19 days (range four to 67 days) in conventionally treated patients. Thus converting enzyme inhibitor therapy may reduce intra hospital mortality in Black Africans hospitalized for congestive heart failure and shorten hospital stay, despite the epidemiologically low plasma renin in Blacks. Hyponatremia may be a poor prognostic index in heart failure in our patients, and its reversal by converting enzyme inhibitors may reflect neurohormonal inhibitor. Earlier and more wide spread use of angiotensin converting enzyme inhibitors in Nigerian and Black Africans with chronic heart failure is now clearly indicated.